1954
DOI: 10.1104/pp.29.3.229
|View full text |Cite
|
Sign up to set email alerts
|

The Absorption of Inorganic Ions by Chlorella pyrenoidosa.

Abstract: GREGORY ET AL-CO2 AND PHOTOPERIODISM metabolism and photoperiodism. Thesis In the course of experiments on the effect of radioactive elements on the growth of Chlorella pyrenoidosa, Porter and Knauss (9), determinations were made of the content of a radioactive element in algal cells when the ratio of that element to its stable isotope was kept constant, but the total concentration of the two isotopes in the solution was varied. Calculations were then made, assuming no isotope effect, of the total contents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0

Year Published

1954
1954
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 11 publications
(14 reference statements)
5
23
0
Order By: Relevance
“…In a previous paper (21), we presented data obtained when water was allowed to evaporate through commercial screens, and interpreted the results in terms of stomatal diffusion. The rule proposed by Brown and Escombe (3) and others (11,23) New screens made to our order, with pores 2.5 to 80 ,u in diameter and, for some sizes, 10 to 160 diameters apart, have enabled us to survey the problem of multiperforate diffusion in considerably greater detail than has previously been possible.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a previous paper (21), we presented data obtained when water was allowed to evaporate through commercial screens, and interpreted the results in terms of stomatal diffusion. The rule proposed by Brown and Escombe (3) and others (11,23) New screens made to our order, with pores 2.5 to 80 ,u in diameter and, for some sizes, 10 to 160 diameters apart, have enabled us to survey the problem of multiperforate diffusion in considerably greater detail than has previously been possible.…”
Section: Discussionmentioning
confidence: 98%
“…In most nutritional studies the effect of treatmlents were estimated by some measurement of net growth (6,12) ; only in some cases was the change in internal composition nmeasured ( 11,21,22). Thus, in many studies the actual cause of the observed changes or the lack of response to treatments is difficult to ascertain.…”
mentioning
confidence: 99%
“…Previous studies of zinc uptake by algae have been conducted by Knauss and Porter ( 1954), who found that the amount of Zn@ absorbed by Chlorella cultures varied with the concentration of zinc in the media. Rice ( 1958) reported a rapid and almost complete absorption of Zns5 by Nitzschia cultures in both the light and the dark, with resulting cell concentration factors up to 58,000.…”
Section: Introductionmentioning
confidence: 99%
“…Deviations fromii this general rule can be causecl by a variety of circunmstances ancl range from a reported independence of concentration over a wide range for ioIn uptake by rye plants ( 10) to a (lirect proportionality to concentration for uptake of several ions 1y Clhlorella (7). A unique anonmaly in whiclh chloride uptake by potato disks at 00, resenmbled an exponential function of concentration was b)rieflv noted b1 Laties (8) and lhas now been further investigated.…”
mentioning
confidence: 99%